"New Normal"- Corona era - Aprajita Mehta; Yogesh Bahurupi; Mahendra Singh; Pradeep Aggarwal (Indian Association of Preventive and Social Medicine, 2020)
Word 'Normal' according to Cambridge dictionary means usual or the same as would be expected. So, when the things change from what is usually expected in a day to day life and the change is going to stay for long it becomes the 'New Normal'. This has been experienced globally after the COVID-19 Pandemic. Things which were very usual and considered normal like travelling in a public transport, greeting people with handshakes or hugs, eating out in a crowded restaurantand roaming in markets or malls suddenly became a threat for the spread of the coronavirus. Terms like quarantine, isolation, lockdown, physical distancing etc. were now used more commonly.